2014
DOI: 10.1186/1756-0500-7-211
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of multi-resistant gram-negative bacteria colonizing chronic lower limb ulcers (CLLUs) at Bugando Medical Center

Abstract: BackgroundInfections, trauma, malignances and poorly controlled diabetes are common causes of chronic lower limb ulcerations in developing countries. Infected wound with multi-drug resistant bacteria usually are associated with increased morbidity and mortality. We report the distribution of bacteria pathogens colonizing the chronic lower limb ulcers and their drug susceptibility pattern from Bugando Medical Centre (BMC) a tertiary hospital in Tanzania.FindingsThree hundred non-repetitive wound swabs were asep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 19 publications
6
28
0
Order By: Relevance
“…The general proportion of MRSA in this study was found to be in agreement with MRSA proportion observed in other studies done in the same setting in 2010 and 2014 [12, 14]. However, during the observation period a significant decrease was observed in 2015, this could be explained by the ongoing hand washing campaigns and improvement of IPC programs in various BMC wards coupled by increased awareness of the emergence of multidrug-resistant strains among healthcare workers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The general proportion of MRSA in this study was found to be in agreement with MRSA proportion observed in other studies done in the same setting in 2010 and 2014 [12, 14]. However, during the observation period a significant decrease was observed in 2015, this could be explained by the ongoing hand washing campaigns and improvement of IPC programs in various BMC wards coupled by increased awareness of the emergence of multidrug-resistant strains among healthcare workers.…”
Section: Discussionsupporting
confidence: 90%
“…As in previous study [14], most of the Pseudomonas aeruginosa isolates in this study were recovered from wound swabs and more than 50% were resistant to third generation cephalosporins. The majority of Pseudomonas aeruginosa isolates in this study were sensitive to amikacin, as previously observed [32].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Similarly other studies have shown the predominance of Gram negative bacteria [3739] and of recent Pseudomonas aeruginosa is reported at BMC as the commonest bacteria colonizing patients with chronic lower limb ulcers [40]; connoting the possibility of nosocomial transmission if stringent infection control and prevention are not adhered in this setting. Similar to another study done in Uganda, the majority of isolates showed high sensitivities to less used antimicrobial agents (gentamicin, ciprofloxacin, cefepine and meropenem) as opposed to commonly used agents (ampicillin, trimethoprim sulphamethoxazole and ceftriaxone) exemplifying the need to have laboratory guided antimicrobial therapy in this setting [38].…”
Section: Discussionmentioning
confidence: 69%
“…Such high AMR rates detected in the isolates from gut contents of wild fish are of concern and indicate strong anthropogenic environmental contamination of the Lake Victoria. The presence of ESBL isolates in the environmental samples suggests that the Lake Victoria is being contaminated by sewage from the hospitals and from animals (Mshana et al, 2009; Kayange et al, 2010; Moremi et al, 2014; Seni et al, 2016). Farming activities that use of animal manure together with agricultural waste from the community generate steady contaminated effluents along the borders of Lake Victoria.…”
Section: Discussionmentioning
confidence: 99%